واقع إصلاح نظام المحاسبة العمومية ودوره في تفعيل التدقيق الحكومي في الجزائر (دراسة حالة قطاع الصحة العمومية لولاية غرداية خلال الفترة : 2010- 2019) (مجلة الواحات للبحوث والدراسات, 2020)
This study aims to highlight on the reality of the public accounting system in Algeria, And The role of accounting reform in activating the public sector audit for the period from 2010 to 2019, Therefore, the sample selection of 07 public health institutions, including 05 in Ghardaia Province concerned on the Application 03COH system, Based on the direct interview method, we concluded that the application of this system is primarily aimed at improving the quality of public sector audits and thus enhancing public governance. And then circulate the system to other sectors starting from 2023 under organic law 18-15 on financial laws, Involving Authorised auditors in the public sector audits Mission. Key words- Public Accounting, reform, public sector audits, Public health sector.